Laminated body
By using the active energy ray curable composition of the cationic polymerizable compound and the photocationic polymerization initiator, the problem of insufficient adhesion and durability between the polarizing film and the phase difference layer is solved, and the optical of high adhesion and durability is achieved Laminated body, suitable for image display and organic electroluminescent display devices.
Patent Information
- Application Number
- CN202080089776.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-22
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-12-22
AI Technical Summary
In the prior art, the adhesion between the polarizing film and the phase difference layer is insufficient and the durability is poor, so it cannot meet the high-performance optical laminate needs.
Using an active energy ray curable composition composed of a cationic polymerizable compound and a photocationic polymerization initiator as the adhesive layer, combined with oxetane and anthracene compounds, a laminated structure with high adhesion and durability is formed by ultraviolet curing. .
Good adhesion and excellent durability between the polarizing film and the phase difference layer are achieved, the performance of the optical laminate is improved, and it is suitable for image display devices and organic electroluminescent display devices.
Smart Images

Figure CN114868051B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate, and further relates to an image display device including the laminate. Background Art
[0002] In image display devices, a method is adopted in which an optical layered body having an antireflection property is arranged on the viewing side of an image display panel to suppress a decrease in visibility due to reflection of external light.
[0003] As an optical laminate having antireflection performance, a laminate composed of a polarizing film and a retardation layer is known. Patent Document 1 proposes a laminate in which a polarizing film and a retardation layer are bonded via an adhesive layer composed of an active energy ray-curable adhesive composition.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2017 / 183333 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In the laminate proposed in Patent Document 1, the adhesion between the polarizing film and the retardation layer is not sufficient, and the durability is also not satisfactory.
[0009] An object of the present invention is to provide a laminated body including a polarizing film and a retardation layer, wherein the polarizing film and the retardation layer have good adhesion and excellent durability.
[0010] Means for solving problems
[0011] The present invention provides the following [1] to
[20] .
[0012] [1] A laminate comprising a polarizing film, a first cured layer, and a first retardation layer laminated in this order, wherein the first retardation layer has a thickness of 10 μm or less, and the first cured layer comprises a cured product of a first active energy ray-curable composition.
[0013] The first active energy ray-curable composition comprises (A) a cationically polymerizable compound and (B) a photocationic polymerization initiator, and
[0014] The (B) photocationic polymerization initiator is contained in an amount of 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the cationically polymerizable compound (A),
[0015] The cationically polymerizable compound (A) contains 45% by mass or more of an oxetane compound based on the total mass of the cationically polymerizable compound (A).
[0016] [2] The laminate according to [1], wherein the first active energy ray-curable composition contains (C) 0.1 to 3.0 parts by mass of a photosensitizer having a maximum absorption for light having a wavelength greater than 400 nm, based on 100 parts by mass of the cationically polymerizable compound (A);
[0017] The photosensitizer (C) includes an anthracene compound represented by the following general formula (I).
[0018]
[0019] (Where R 1 and R 2 each independently represents an alkyl group having 1 to 6 carbon atoms or an alkoxyalkyl group having 2 to 12 carbon atoms, and R 3 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. )
[0020] [3] The laminate according to [1] or [2], wherein the oxetane compound is at least one selected from 3-ethyl-3-hydroxymethyloxetane, xylenebisoxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and 3-ethyl-3-(cyclohexyloxymethyl)oxetane.
[0021] [4] The laminate according to any one of [1] to [3], wherein the cationically polymerizable compound (A) contains 10% by mass or more and 50% by mass or less of an alicyclic epoxy compound based on the total mass of the cationically polymerizable compound (A).
[0022] [5] The laminate according to any one of [1] to [4], wherein the photocationic polymerization initiator (B) is at least one ionic compound selected from aromatic sulfonium salts and aromatic iodonium salts.
[0023] [6] The laminate according to any one of [1] to [5], wherein the viscosity of the first active energy ray-curable composition at 25° C. is 200 mPa·s or less.
[0024] [7] The laminate according to any one of [1] to [6], wherein the first active energy ray-curable composition satisfies the following formula (1):
[0025] (J A / J B )×100≥60(%) (1)
[0026] [J A It represents the heat amount (unit: mJ / g) measured by a differential scanning calorimeter when ultraviolet rays having a peak at a wavelength of 365 nm are irradiated to the first active energy ray-curable composition through a substrate having a light transmittance of 0% to 10% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm.
[0027] J B It represents the amount of heat (mJ / g) measured by a differential scanning calorimeter when ultraviolet rays having a peak at a wavelength of 365 nm are irradiated to the first active energy ray-curable composition without passing through the substrate.]
[0028] [8] The laminate according to any one of [1] to [7], wherein the storage modulus of the first cured product layer at 80° C. is 300 MPa or more.
[0029] [9] The laminate according to any one of [1] to [8], wherein the thickness of the first cured product layer is 0.5 μm or more and 10 μm or less.
[0030]
[10] The laminate according to any one of [1] to [9], wherein the first retardation layer has a light transmittance of 0% to 50% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm.
[0031]
[11] The laminate according to any one of [1] to
[10] , wherein the first retardation layer has a light transmittance of 0% to 10% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm.
[0032]
[12] The laminate according to any one of [1] to
[11] , wherein a second cured material layer and a second retardation layer are sequentially laminated on the side of the first retardation layer opposite to the first cured material layer,
[0033] The second cured layer includes a cured product of a second active energy ray-curable composition, and at least one of the first retardation layer and the second retardation layer has a light transmittance of 0% to 10% at a wavelength of 380nm and a light transmittance of 30% or more at a wavelength of 400nm.
[0034]
[13] The laminate according to
[12] , wherein the first retardation layer is a 1 / 2 wavelength retardation layer, and the second retardation layer is a 1 / 4 wavelength retardation layer.
[0035]
[14] The laminate according to
[12] , wherein the first retardation layer is a 1 / 2 wavelength retardation layer or a 1 / 4 wavelength retardation layer, and the second retardation layer is a positive C plate.
[0036]
[15] The laminate according to any one of
[12] to
[14] , wherein at least one of the first retardation layer and the second retardation layer includes a liquid crystal layer having retardation-appearing properties.
[0037]
[16] The laminate according to any one of
[12] to
[15] , wherein a thickness of at least one of the first retardation layer and the second retardation layer is greater than or equal to 0.5 μm and less than or equal to 50 μm.
[0038]
[17] A circularly polarizing plate comprising the laminate according to any one of [1] to
[16] .
[0039]
[18] An image display device comprising an image display panel and the laminate according to any one of [1] to
[16] disposed on a viewing side of the image display panel.
[0040]
[19] The image display device according to
[18] , wherein the stacked body is arranged in an orientation in which the polarizing film is located on the viewing side.
[0041]
[20] An organic electroluminescent display device comprising the image display device described in
[18] or
[19] .
[0042] Effects of the Invention
[0043] According to the present invention, there can be provided a laminated body including a polarizing film and a retardation layer, wherein the polarizing film and the retardation layer have good adhesion and excellent durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] [ Figure 1 ] is a schematic cross-sectional view schematically showing the laminate of the present invention.
[0045] [ Figure 2 ] is a schematic cross-sectional view schematically showing a phase difference layer.
[0046] [ Figure 3 ] is a schematic cross-sectional view schematically showing the laminate of the present invention.
[0047] [ Figure 4 ] is a schematic cross-sectional view schematically showing an example of each manufacturing step in a method for manufacturing a laminate. DETAILED DESCRIPTION
[0048] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to the following embodiments. In all the following drawings, in order to facilitate understanding of each component, the scale is appropriately adjusted for representation, and the scale of each component shown in the drawings is not necessarily consistent with the scale of the actual component.
[0049] <Laminate>
[0050] For the laminate of the present invention, refer to Figure 1 And explain. Figure 1 The laminated body 100 shown has a polarizing film 11 , a first cured material layer 12 , and a first retardation layer 13 laminated in this order.
[0051] The thickness of the laminate 100 may be, for example, 3 μm or more and 100 μm or less, and preferably 3 μm or more and 60 μm or less.
[0052] The laminate 100 may be in the form of a strip or a single sheet. When the laminate 100 is in the form of a single sheet, the shape of the laminate 100 when viewed from above may be substantially rectangular. Viewed from above means viewed from the thickness direction of the laminate 100. Substantially rectangular means that the shape may be as follows: a shape in which at least one of the four corners (corners) is cut off in an obtuse manner or a shape provided with an arc; a part of the end face when viewed from above has a concave portion (cutout) that is sunken inwardly in the plane; or a part of the shape when viewed from above has a perforated portion that is hollowed out into a circular, elliptical, polygonal, or a combination thereof.
[0053] The size of the laminate 100 is not particularly limited. If the laminate 100 is a single sheet and substantially rectangular, the length of the long side is preferably 6 cm to 35 cm, more preferably 10 cm to 30 cm, and the length of the short side is preferably 5 cm to 30 cm, more preferably 6 cm to 25 cm.
[0054] (Polarizing Film)
[0055] The polarizing film 11 may be an absorption-type polarizer, which has the property of absorbing linear polarized light having a vibration plane parallel to its absorption axis and transmitting linear polarized light having a vibration plane orthogonal to the absorption axis (parallel to the transmission axis). As the polarizing film 11, a polarizer in which a dichroic dye is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol resin film may be preferably used. The polarizing film 11 may be manufactured, for example, by a method including the following steps: a step of uniaxially stretching the polyvinyl alcohol resin film; a step of adsorbing the dichroic dye by dyeing the polyvinyl alcohol resin film with a dichroic dye; a step of treating the polyvinyl alcohol resin film adsorbed with the dichroic dye with a crosslinking liquid such as an aqueous boric acid solution; and a step of washing with water after the treatment with the crosslinking liquid.
[0056] As the polyvinyl alcohol-based resin, a resin obtained by saponifying a polyvinyl acetate-based resin can be used. As the polyvinyl acetate-based resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers with other monomers copolymerizable with vinyl acetate can be cited. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group.
[0057] In the present specification, "(meth)acrylic acid" means at least one selected from acrylic acid and methacrylic acid. The same applies to "(meth)acryloyl", "(meth)acrylate" and the like.
[0058] The saponification degree of the polyvinyl alcohol resin is usually 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes may be used. The average degree of polymerization of the polyvinyl alcohol resin is usually 1000 to 10000, preferably 1500 to 5000. The average degree of polymerization of the polyvinyl alcohol resin can be obtained according to JIS K 6726.
[0059] The product obtained by film-forming such a polyvinyl alcohol resin can be used as a raw material film for a polarizer. The method for film-forming the polyvinyl alcohol resin is not particularly limited, and a known method can be used. The thickness of the polyvinyl alcohol raw material film is not particularly limited. For example, in order to make the thickness of the polarizer less than 15 μm, it is preferred to use a raw material film of 5 μm or more and 35 μm or less. More preferably, it is less than 20 μm.
[0060] The uniaxial stretching of the polyvinyl alcohol-based resin film can be carried out before the dyeing of the dichroic pigment, simultaneously with the dyeing, or after the dyeing. In the case of carrying out uniaxial stretching after dyeing, the uniaxial stretching can be carried out before the crosslinking treatment or in the crosslinking treatment. In addition, uniaxial stretching can also be carried out in these multiple stages.
[0061] During uniaxial stretching, the film may be stretched uniaxially between rollers having different circumferential speeds, or may be stretched uniaxially using a heated roller. In addition, the uniaxial stretching may be dry stretching in the air, or wet stretching in a state where the polyvinyl alcohol resin film is swollen using a solvent or water. The stretching ratio is usually 3 to 8 times.
[0062] As the method for dyeing the polyvinyl alcohol resin film with a dichroic pigment, for example, the method of immersing the film in an aqueous solution containing a dichroic pigment can be adopted. As the dichroic pigment, iodine or a dichroic organic dye can be used. It should be noted that the polyvinyl alcohol resin film is preferably immersed in water before the dyeing process.
[0063] As a crosslinking treatment after dyeing with a dichroic dye, a method of immersing the dyed polyvinyl alcohol-based resin film in an aqueous solution containing boric acid can generally be adopted. When iodine is used as the dichroic dye, the aqueous solution containing boric acid preferably contains potassium iodide.
[0064] The thickness of the polarizing film 11 is usually 30 μm or less, preferably 28 μm or less, more preferably 20 μm or less, further preferably 15 μm or less, particularly preferably 10 μm or less. The thickness of the polarizing film 11 is usually 2 μm or more, preferably 3 μm or more.
[0065] As the polarizing film 11 , for example, as described in Japanese Patent Application Laid-Open No. 2016-170368, a film in which a dichroic dye is oriented in a cured film formed by polymerizing a liquid crystal compound may be used.
[0066] As dichroic pigment, can use the dichroic pigment with absorption in the scope of wavelength above 380nm and below 800nm, preferably use organic dye.As dichroic pigment, for example can enumerate azo compound.Liquid crystal compound is the liquid crystal compound that can be polymerized while keeping orientation, can have polymerizable group in molecule.In addition, also can form polarizer by the dichroic pigment with liquid crystallinity as described in WO2011 / 024891.
[0067] (First Cured Material Layer)
[0068] The first cured layer 12 is arranged between the polarizing film 11 and the first phase difference layer 13 in order to bond the polarizing film 11 to the first phase difference layer 13. The first cured layer 12 contains a cured product of the first active energy ray-curable composition. The first cured layer 12 contains a cured product of the first active energy ray-curable composition, so that there is a tendency to easily obtain good durability and adhesion. In the present invention, the evaluation of durability and adhesion is carried out according to the method described in the embodiment column described later.
[0069] The thickness of the first cured material layer 12 may be, for example, 10 μm or less, preferably 8 μm or less, more preferably 7 μm or less, further preferably 6 μm or less, and particularly preferably 4 μm or less. The thickness of the first cured material layer 12 may be, for example, 0.5 μm or more, preferably 1 μm or more, and more preferably 2 μm or more.
[0070] (First active energy ray-curable composition)
[0071] The first active energy ray-curable composition is a cationically polymerizable composition that is cured by irradiating active energy rays. The first active energy ray-curable composition contains 1 part by mass or more and 10 parts by mass or less of a photocationic polymerization initiator (B) relative to 100 parts by mass of the cationically polymerizable compound (A). The first active energy ray-curable composition preferably further contains 0.1 parts by mass or more and 3.0 parts by mass or less of a photosensitizer (C) that exhibits maximum absorption for light having a wavelength greater than 400 nm relative to 100 parts by mass of the cationically polymerizable compound (A).
[0072] (Cationically polymerizable compound (A))
[0073] The cationic polymerizable compound (A) is a component that can be cured by cation polymerization by irradiation with active energy rays. Adhesion is manifested by polymerization curing of the cationic polymerizable compound (A). The cationic polymerizable compound (A) contains 45% by mass or more of the oxetane compound (A1) based on the total mass of the cationic polymerizable compound (A). By including 45% by mass or more of the oxetane compound (A1) in the first active energy ray curable composition, the viscosity of the active energy ray curable composition is reduced, so there is a tendency that the coating of the film is easy to carry out, the elastic modulus of the cured product is improved, and good durability is easy to obtain.
[0074] (Oxetane compound (A1))
[0075] In the present specification, the oxetane compound (A1) is a compound having an oxetane group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound (A1) referred to in the present specification is a compound not having an epoxy group.
[0076] The oxetane compound (A1) may be a monofunctional oxetane compound having only one oxetane group, or may be a polyfunctional oxetane compound having two or more oxetane groups. The oxetane compound (A1) is preferably a polyfunctional oxetane compound, preferably a bifunctional oxetane compound having two oxetane groups.
[0077] Specific examples of the oxetane compound (A1) include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether,
[0063] In some embodiments, the oxetane compound (A1) may be 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, xylylenebisoxetane, and the like. As the oxetane compound (A1), one oxetane compound may be used alone, or different oxetane compounds may be used in combination. Among them, at least one selected from 3-ethyl-3-hydroxymethyloxetane, xylenebisoxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and 3-ethyl-3-(cyclohexyloxymethyl)oxetane is preferred.
[0078] As the oxetane compound (A1), commercially available products can be used. For example, the trade names include "Aron Oxetane (registered trademark)" series sold by Toagosei Co., Ltd. and "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.
[0079] Based on the total mass of the cationic polymerizable compound (A), the content of the oxetane compound (A1) in the cationic polymerizable compound (A) is 45% by mass or more, preferably 50% by mass or more, more preferably 55% by mass or more, and further preferably 60% by mass or more. The content of the oxetane compound (A1) in the cationic polymerizable compound (A) is, for example, 90% by mass or less, preferably 80% by mass or less, and further preferably 75% by mass or less. If the content of the oxetane compound (A1) is 90% by mass or less, there is a tendency that the reduction in adhesion is not easy to occur.
[0080] In addition, when the oxetane compound (A1) contains a polyfunctional oxetane compound and a monofunctional oxetane compound, based on the total mass of the oxetane compound (A1), it is preferred that the polyfunctional oxetane compound be contained in an amount of 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.
[0081] (Other cationically polymerizable compounds)
[0082] The cationically polymerizable compound (A) may further contain at least one selected from the group consisting of an alicyclic epoxy compound (A2), an aliphatic epoxy compound (A3), and an aromatic epoxy compound (A4).
[0083] In the case where the cationic polymerizable compound (A) contains an alicyclic epoxy compound (A2), the content of the alicyclic epoxy compound (A2) is, for example, 10 parts by mass or more and 50 parts by mass or less, preferably 10 parts by mass or more and 40 parts by mass or less, more preferably 10 parts by mass or more and 35 parts by mass or less, and further preferably 10 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the cationic polymerizable compound (A). In the case where the content of the alicyclic epoxy compound (A2) is 10 parts by mass or more, there is a tendency that the curing speed of the cationic polymerizable compound is not easily reduced. In addition, in the case where the content of the alicyclic epoxy compound (A2) is 50 parts by mass or less, there is a tendency to suppress the viscosity increase of the cationic polymerizable compound and facilitate thin film coating.
[0084] When the cationically polymerizable compound (A) contains an aliphatic epoxy compound (A3), the content of the aliphatic epoxy compound (A3) can be, for example, 1 part by mass or more and 50 parts by mass or less, and is preferably 2.5 parts by mass or more and 40 parts by mass or less, and more preferably 5 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the cationically polymerizable compound (A).
[0085] When the cationically polymerizable compound (A) contains an aromatic epoxy compound (A4), the content of the aromatic epoxy compound (A4) is, for example, 10 parts by mass or more and 50 parts by mass or less, preferably 15 parts by mass or more and 40 parts by mass or less, and more preferably 20 parts by mass or more and 30 parts by mass or less, relative to 100 parts by mass of the cationically polymerizable compound (A). When the content of the aromatic epoxy compound (A4) is 50 parts by mass or less, there is a tendency that a decrease in adhesion is less likely to occur.
[0086] By using an oxetane compound (A1) and an alicyclic epoxy compound (A2) together, the curing speed of the cationic polymerizable compound (A) is improved. The ratio is oxetane compound (A1): alicyclic epoxy compound (A2) = 4:1 to 1:1, more preferably 3:1 to 1:1, and more preferably 2:1 to 1:1. If it is within the above range, curing can be carried out efficiently, and the obtained cured product has a dense cross-linked structure.
[0087] The first active energy ray-curable composition preferably does not contain a solvent.
[0088] (Alicyclic epoxy compound (A2))
[0089] The alicyclic epoxy compound (A2) is a compound having one or more alicyclic epoxy groups.
[0090] As long as the alicyclic epoxy compound (A2) is a compound having one or more alicyclic epoxy groups, it may further have an epoxy group other than the alicyclic epoxy group. In this specification, the alicyclic epoxy group means an epoxy group bonded to an alicyclic ring, and means a bridging oxygen atom -O- in the structure represented by the following formula (a).
[0091]
[0092] In the above formula (a), m is an integer of 2 to 5. The above formula (a) without (CH2) m The compound obtained by bonding the group formed after one or more hydrogen atoms in the (CH2) with other chemical structures can become an alicyclic epoxy compound (A2). m One or more hydrogen atoms in the alicyclic epoxy compound (A2) may be appropriately substituted with a linear alkyl group such as a methyl group or an ethyl group. The curing rate of the first active energy ray-curable composition can be adjusted by the alicyclic epoxy compound (A2).
[0093] Specific examples of the alicyclic epoxy compound (A2) include 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-1-methyl-4-(1-methylepoxyethyl)cyclohexane, 3,4-epoxycyclohexylmethyl methacrylate, 4-(1,2-epoxyethyl)-1,2-epoxycyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, ethylenebis(3,4-epoxycyclohexanecarboxylate), oxydiethylenebis(3,4-epoxycyclohexanecarboxylate), 1,4-cyclohexanedimethylbis(3,4-epoxycyclohexanecarboxylate), and 3-(3,4-epoxycyclohexylmethoxycarbonyl)propyl 3,4-epoxycyclohexanecarboxylate.
[0094] Among the alicyclic epoxy compounds (A2), 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate is preferably used because it has moderate curability and can be obtained at a relatively low cost. As the alicyclic epoxy compound (A2), one alicyclic epoxy compound may be used alone or in combination of different alicyclic epoxy compounds.
[0095] The alicyclic epoxy compound (A2) may be a commercially available product. Examples of the products include "Celoxide (registered trademark)" series and "EHPE3150" and "Cyclomer (registered trademark)" sold by DAICEL Co., Ltd. and "Cyracure UVR" series sold by DOW Chemical Co., Ltd.
[0096] In the present invention, the aliphatic epoxy compound (A3) includes a monofunctional aliphatic epoxy compound (A3-1) having one epoxy group and a polyfunctional aliphatic epoxy compound (A3-2) having two or more epoxy groups. From the viewpoint of maintaining the cohesive force of the cured product and improving the adhesion, the polyfunctional aliphatic epoxy compound is preferred.
[0097] The monofunctional aliphatic epoxy (A3-1) can adjust the viscosity of the first active energy ray-curable composition.
[0098] As monofunctional aliphatic epoxy (A3-1), glycidyl ethers of aliphatic alcohols, glycidyl esters of alkyl carboxylic acids, etc. can be cited, and specific examples thereof include allyl glycidyl ether, butyl glycidyl ether, sec-butylphenyl glycidyl ether, 2-ethylhexyl glycidyl ether, C12 and C13 mixed alkyl glycidyl ethers, glycidyl ethers of alcohols, monoglycidyl ethers of aliphatic higher alcohols, glycidyl esters of higher fatty acids, etc. As monofunctional aliphatic epoxy (A3-1), one monofunctional epoxy compound may be used alone, or different types thereof may be used in combination.
[0099] The polyfunctional aliphatic epoxy (A3-2) is a compound having two or more epoxy groups and no aromatic ring. However, the polyfunctional aliphatic epoxy (A3-2) mentioned in this specification does not include compounds having alicyclic epoxy groups contained in the alicyclic epoxy compound (A2). The polyfunctional aliphatic epoxy (A3-2) can adjust the adhesion of the adhesive cured layer.
[0100] As the polyfunctional aliphatic epoxy (A3-2), an aliphatic diepoxy compound represented by the following formula (b) is more preferred. By including an aliphatic diepoxy compound represented by the following formula (b) as the polyfunctional aliphatic epoxy compound (A3), an active energy ray-curable adhesive having low viscosity and being easy to apply can be obtained.
[0101]
[0102] In formula (b), Z is an alkylene group having 1 to 9 carbon atoms, an alkylidene group having 3 or 4 carbon atoms, a divalent alicyclic hydrocarbon group, or a group of the formula -C m H 2m -Z 1 -C n H 2n - is a divalent group. m H 2m -Z 1 -C n H 2n -Z 1 - is -O-, -CO-O-, -O-CO-, -SO2-, -SO- or CO-, m and n each independently represent an integer greater than 1, and the total of m and n is 9 or less.
[0103] The divalent alicyclic hydrocarbon group may be, for example, a divalent alicyclic hydrocarbon group having 4 to 8 carbon atoms, and examples thereof include a divalent group represented by the following formula (b-1).
[0104]
[0105] Specific examples of the compound represented by formula (b) include diglycidyl ethers of alkanediols, diglycidyl ethers of oligoalkylene glycols having a repeating number of up to about 4, and diglycidyl ethers of alicyclic diols.
[0106] Examples of glycols that can form the compound represented by the above formula (b) include ethylene glycol, propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-2,4-pentanediol, 2,4-pentanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, Alkanediols such as diol, 2-methyl-2,4-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 3,5-heptanediol, 1,8-octanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol; oligomeric alkylene glycols such as diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol; alicyclic diols such as cyclohexanediol and cyclohexanedimethanol.
[0107] From the viewpoint of obtaining a first active energy ray-curable composition having low viscosity and easy coating, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether are preferred. As the aliphatic epoxy compound (A3), one aliphatic epoxy compound may be used alone or in combination of different aliphatic epoxy compounds.
[0108] As the aliphatic epoxy compound (A3), commercially available products may be used, and examples thereof include "EP-4088S", "ED-523T" (both manufactured by ADEKA Corporation), "EX-211L", and "EX-212L" (both manufactured by Nagase ChemteX Corporation).
[0109] Aromatic Epoxides (A4)
[0110] The aromatic epoxy compound (A4) includes a monofunctional aromatic epoxy compound (A4-1) having one epoxy group, and a polyfunctional aromatic epoxy compound (A4-2) having two or more epoxy groups. However, the aromatic epoxy compound (A4) in the present invention does not include a compound having an alicyclic epoxy group in the molecule, as contained in the alicyclic epoxy compound (A2).
[0111] Examples of the monofunctional aromatic epoxy (A4-1) include monoglycidyl ethers of monophenols such as phenol, cresol, and butylphenol, or bisphenol derivatives such as bisphenol A and bisphenol F, or their alkylene oxide adducts; epoxy novolac resins; monoglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups such as resorcinol, hydroquinone, and catechol; monoglycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups such as benzyl alcohol, benzyl alcohol, and benzyl butanol; monoglycidyl esters of polyacid aromatic compounds having two or more carboxyl groups such as phthalic acid, terephthalic acid, and trimellitic acid; glycidyl esters of benzoic acid, monoglycidyl esters of toluic acid, and monoglycidyl esters of naphthoic acid;
[0112] As the monofunctional aromatic epoxy (A4-1), commercially available products can be used, and examples thereof include "EX-142", "EX-146", "EX-147", and "EX-121" (all of which are manufactured by Nagase ChemteX Corporation).
[0113] Specific examples of the polyfunctional aromatic epoxy (A4-2) include polyglycidyl ethers of naphthalene or naphthalene derivatives (also referred to as "naphthalene-type epoxy compounds"); polyglycidyl ethers of bisphenol derivatives such as bisphenol A and bisphenol F (also referred to as "bisphenol A-type epoxy compounds" and "bisphenol F-type epoxy compounds"); epoxy novolac resins; polyglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups such as resorcinol, hydroquinone, and catechol; benzyl alcohol Polyglycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups, such as 1,2-diethylbenzene, and 1,2-dibutylbenzene; polyglycidyl esters of polybasic acid aromatic compounds having two or more carboxyl groups, such as phthalic acid, terephthalic acid, and trimellitic acid; glycidyl esters of benzoic acid, toluic acid, and naphthoic acid; phenyl oxiranes such as phenyl oxiranes, alkylated phenyl oxiranes, and epoxides of vinyl naphthalene, or diepoxides of divinylbenzene, etc. As the polyfunctional aromatic epoxy (A4-2), one compound may be used alone, or different compounds may be used in combination.
[0114] As the polyfunctional aromatic epoxy (A4-2), commercially available products can be used, for example, "DENACOL EX-201", "DENACOL EX-711" and "DENACOL EX-721" (all manufactured by Nagase ChemteX Co., Ltd.); "OGSOL EG-280" and "OGSOL CG-400" (all manufactured by Osaka Gas Chemical Co., Ltd.); "EXA-80CRP" and "HP4032D" (all manufactured by DIC Co., Ltd.); "jER828" and "jER828EL" (all manufactured by Mitsubishi Chemical Co., Ltd.); "ADEKA RESIN EP-4100", "ADEKA RESIN EP-4100G", "ADEKA RESIN EP-4100E", "ADEKA RESIN EP-4100L", "ADEKA RESIN EP-4100TX", "ADEKA RESIN EP-4000", "ADEKA RESIN EP-4005", "ADEKA RESIN EP-4901", "ADEKA RESIN EP-4901E" (all manufactured by ADEKA Co., Ltd.), etc.
[0115] In order to make the first active energy ray-curable composition solvent-free, the curable components [oxetane compound (A1), alicyclic epoxy compound (A2), aliphatic epoxy compound (A3), aromatic epoxy compound (A4)] are preferably used without being diluted with an organic solvent or the like.
[0116] The curable component is usually selected to be a liquid at room temperature, has moderate fluidity even in the absence of a solvent, and imparts appropriate bonding strength. The first active energy ray-curable composition with a photocationic polymerization initiator adapted thereto can omit a drying device for evaporating the solvent in the process of bonding the linear polarizing plate and the phase difference layer laminate in the manufacturing equipment of the optical laminate. In addition, by irradiating an appropriate amount of active energy rays, the curing speed can be accelerated, thereby increasing the production speed.
[0117] (Other curing ingredients)
[0118] The cationically polymerizable compound (A) contained in the first active energy ray-curable composition is not limited to the above-mentioned curable components, and may also contain cationically polymerizable curable components other than the above-mentioned cationically polymerizable curable components and free radical polymerizable curable components. Examples of free radical polymerizable curable components include acrylic compounds.
[0119] However, since radical polymerization tends to cause large shrinkage during curing, the first active energy ray-curable composition preferably contains only a cationically polymerizable curable component as the cationically polymerizable compound (A).
[0120] (Photocationic polymerization initiator (B))
[0121] The first active energy ray-curable composition contains a photocationic polymerization initiator (B), whereby the cationically polymerizable compound (A) can be cured by cationic polymerization due to irradiation with active energy rays to form an adhesive layer.
[0122] By containing more than 1 mass part of photocationic polymerization initiator (B), it is possible to fully cure the curable component, and it is possible to obtain an adhesive cured layer with sufficient bonding strength and hardness. On the other hand, if its amount increases, the ionic substance in the cured product increases, and the hygroscopicity of the cured product becomes high, and there is a possibility of reducing the durability of the laminate, so the amount of photocationic polymerization initiator (B) is set to less than 10 mass parts relative to the total amount of 100 mass parts of cationic polymerizable compounds (A). Relative to the total amount of 100 mass parts of cationic polymerizable compounds (A), the content of the photocationic polymerization initiator (B) in the first active energy ray curable composition is preferably more than 1.5 mass parts and less than 8 mass parts, more preferably more than 2 mass parts and less than 6 mass parts.
[0123] The photocationic polymerization initiator (B) is a substance that generates cationic species or Lewis acids by irradiation with active energy rays such as visible light, ultraviolet rays, X-rays, and electron beams, and initiates the polymerization reaction of the cationic polymerizable compound (A). Since the photocationic polymerization initiator (B) acts as a catalyst by light, it has excellent storage stability and handleability even when mixed with the cationic polymerizable compound (A). Examples of compounds that can be used as the photocationic polymerization initiator (B) and that generate cationic species and Lewis acids by irradiation with active energy rays include aromatic diazonium salts; aromatic iodonium salts, aromatic sulfonium salts and other onium salts; iron-arene complexes, etc.
[0124] The photocationic polymerization initiator (B) is preferably at least one ionic compound selected from aromatic sulfonium salts and aromatic iodonium salts.
[0125] Examples of the aromatic diazonium salt include benzenediazonium hexafluoroantimonate, benzenediazonium hexafluorophosphate, and benzenediazonium hexafluoroborate.
[0126] Examples of the aromatic iodonium salt include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and bis(4-nonylphenyl)iodonium hexafluorophosphate.
[0127] Examples of the aromatic sulfonium salt include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4'-bis[diphenylsulfonyl]diphenyl sulfide bishexafluorophosphate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]diphenyl sulfide bishexafluoroantimonate, 4,4'-bis[bis(β-hydroxyethoxy)phenylsulfonyl]diphenyl sulfide bishexafluorophosphate, 7-[di(p-toluoyl)sulfonyl] 〕-2-isopropylthioxanthone hexafluoroantimonate, 7-〔di(p-toluoyl)sulfonium〕-2-isopropylthioxanthone tetrakis(pentafluorophenyl)borate, 4-phenylcarbonyl-4'-diphenylsulfonium-diphenyl sulfide hexafluorophosphate, 4-(p-tert-butylphenylcarbonyl)-4'-diphenylsulfonium-diphenyl sulfide hexafluoroantimonate, 4-(p-tert-butylphenylcarbonyl)-4'-di(p-toluoyl)sulfonium-diphenyl sulfide tetrakis(pentafluorophenyl)borate.
[0128] Examples of the iron-arene complex include xylene-cyclopentadienyl iron (II) hexafluoroantimonate, cumene-cyclopentadienyl iron (II) hexafluorophosphate, and xylene-cyclopentadienyl iron (II) tris(trifluoromethanesulfonyl)methanide.
[0129] The photocationic polymerization initiator (B) may be used alone or in combination of two or more. Among the above, aromatic sulfonium salts are preferably used because they have ultraviolet absorption properties in the wavelength region near 300 nm, thereby obtaining an adhesive cured layer with excellent curability, good mechanical strength and bonding strength.
[0130] When a radical polymerizable curable component is contained as the curable component, it is preferred that a radical polymerization initiator is contained as the polymerization initiator in addition to the photocationic polymerization initiator (B).
[0131] (Photosensitizer (C))
[0132] The first active energy ray curable composition contains a photosensitizer (C) (hereinafter, also referred to as photosensitizer (C)) that shows maximum absorption for light with a wavelength greater than 400nm, thereby, compared with the case where the photosensitizer (C) is not contained, the curability of the adhesive can be improved. In addition, even in the bonding of the linear polarizing plate and the phase difference layer stack described later, when the ultraviolet transmittance of the phase difference layer and the adhesive layer between the phase difference layer is low, the active energy ray curable adhesive composition can be cured by irradiating ultraviolet rays from the phase difference layer side. In addition, generally, the linear polarizing plate arranged on the viewing side mostly contains an ultraviolet absorber. In the past, if ultraviolet rays were irradiated from the linear polarizing plate side, the active energy ray curable adhesive composition could not be fully cured. However, by using a specific amount of photosensitizer (C) as in the present invention, the active energy ray curable adhesive composition can also be cured by irradiating active energy rays from the linear polarizing plate side.
[0133] The photosensitizer (C) contains an anthracene compound represented by the following general formula (I).
[0134]
[0135] (Where R 1 and R 2 each independently represents an alkyl group having 1 to 6 carbon atoms or an alkoxyalkyl group having 2 to 12 carbon atoms, and R 3 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. )
[0136] The above-mentioned photocationic polymerization initiator (B) shows maximum absorption in the wavelength region near 300nm or shorter than that, and senses light of the nearby wavelength to produce cationic species or Lewis acid, thereby initiating cationic polymerization of the cationic polymerizable curable component. However, the anthracene compound represented by the general formula (I) shows maximum absorption in the wavelength region greater than 400nm, and thus can also sense light of wavelength greater than 400nm.
[0137] Specific examples of anthracene compounds include:
[0138] 9,10-dimethoxyanthracene,
[0139] 9,10-diethoxyanthracene,
[0140] 9,10-dipropoxyanthracene,
[0141] 9,10-diisopropoxyanthracene,
[0142] 9,10-dibutoxyanthracene,
[0143] 9,10-dipentyloxyanthracene,
[0144] 9,10-Dihexyloxyanthracene,
[0145] 9,10-bis(2-methoxyethoxy)anthracene,
[0146] 9,10-bis(2-ethoxyethoxy)anthracene,
[0147] 9,10-bis(2-butoxyethoxy)anthracene,
[0148] 9,10-bis(3-butoxypropoxy)anthracene,
[0149] 2-methyl or 2-ethyl-9,10-dimethoxyanthracene,
[0150] 2-methyl or 2-ethyl-9,10-diethoxyanthracene,
[0151] 2-methyl or 2-ethyl-9,10-dipropoxyanthracene,
[0152] 2-methyl or 2-ethyl-9,10-diisopropoxyanthracene,
[0153] 2-methyl or 2-ethyl-9,10-dibutoxyanthracene,
[0154] 2-methyl or 2-ethyl-9,10-dipentyloxyanthracene,
[0155] 2-Methyl or 2-ethyl-9,10-diethyloxyanthracene.
[0156] The content of the photosensitizer (C) in the first active energy ray-curable composition is preferably 0.1 to 5.0 parts by mass, more preferably 0.5 to 3.0 parts by mass, relative to 100 parts by mass of the total amount of the cationically polymerizable compound (A).
[0157] (Photosensitizer (D))
[0158] The first active energy ray-curable composition may contain a photosensitizer (D). The photosensitizer (D) is preferably a naphthalene-based photosensitizer.
[0159] Specific examples of naphthalene-based photosensitizers include:
[0160] 4-methoxy-1-naphthol,
[0161] 4-ethoxy-1-naphthol,
[0162] 4-Propoxy-1-naphthol,
[0163] 4-Butoxy-1-naphthol,
[0164] 4-Hexyloxy-1-naphthol,
[0165] 1,4-dimethoxynaphthalene,
[0166] 1-ethoxy-4-methoxynaphthalene,
[0167] 1,4-Diethoxynaphthalene,
[0168] 1,4-dipropoxynaphthalene,
[0169] 1,4-Dibutoxynaphthalene.
[0170] By making the first active energy ray curable composition contain naphthalene-based photosensitizer, compared with the case of not containing naphthalene-based photosensitizer, the curing speed of the adhesive can be increased. Relative to the total amount of 100 parts by mass of the cationically polymerizable compound (A), the content of the naphthalene-based photosensitizer is set to more than 0.1 parts by mass, thus, such an effect can be manifested. On the other hand, if the content of the naphthalene-based photosensitizer becomes more, the problem of precipitation occurs during low temperature storage, so it is preferably set to less than 5 parts by mass relative to the total amount of 100 parts by mass of the cationically polymerizable compound (A). The content of the naphthalene-based photosensitizer is preferably less than 3 parts by mass relative to the total amount of 100 parts by mass of the cationically polymerizable compound (A).
[0171] (Additive ingredient (E))
[0172] The first active energy ray-curable composition may contain an additive component (E) as another optional component as long as the effect of the present invention is not impaired. Examples of the additive component (E) include ion trapping agents, antioxidants, light stabilizers, chain transfer agents, tackifiers, thermoplastic resins, fillers, flow regulators, plasticizers, defoamers, leveling agents, pigments, organic solvents, and the like.
[0173] When the additive component (E) is contained, the content thereof is preferably 10 parts by mass or less based on 100 parts by mass of the total amount of the cationically polymerizable compound (A).
[0174] The photocationic polymerization initiator (B), photosensitizer (C), photosensitizer (D), and additive component (E) can be added in a solvent-free state when preparing the first active energy ray-curable composition, or can be added directly after being diluted with a solvent. The numerical ranges of the above contents are all numerical ranges based on solid content.
[0175] (Viscosity)
[0176] As the viscosity of the first active energy ray curable composition, it is sufficient to have a viscosity that can be applied by various methods, and its viscosity at a temperature of 25° C. is, for example, 200 mPa·s or less, preferably 10 mPa·s or more and 180 mPa·s or less. If its viscosity is too low, there is a tendency that it is difficult to form a layer of the desired thickness. On the other hand, if its viscosity is too high, it is difficult to flow, and there is a tendency that it is difficult to obtain a uniform coating without unevenness. The viscosity mentioned here is a value measured at 10 rpm using an E-type viscometer and adjusting the temperature of the adhesive to 25° C.
[0177] (Curing method)
[0178] The first active energy ray curable composition can be used in the form of an electron beam curable type or an ultraviolet curable type. In this specification, active energy rays are defined as energy rays that can decompose a compound that generates active species to generate active species. Examples of such active energy rays include visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays, and electron beams.
[0179] For electron beam curing, the irradiation conditions of the electron beam can be any appropriate conditions as long as the conditions under which the first active energy ray curable composition can be cured. For example, the acceleration voltage of the electron beam irradiation is preferably 5kV or more and 300kV or less, more preferably 10kV or more and 250kV or less. When the acceleration voltage is less than 5kV, the electron beam cannot reach the adhesive, and there is a concern about insufficient curing. If the acceleration voltage exceeds 300kV, the penetration force through the sample is too strong to rebound the electron beam, and there is a concern about damage to the transparent protective film and the polarizer. The irradiation dose is 5kGy or more and 100kGy or less, more preferably 10kGy or more and 75kGy or less. When the irradiation dose is less than 5kGy, the adhesive becomes insufficiently cured. If it exceeds 100kGy, the optical layer is damaged, resulting in a reduction in mechanical strength and yellowing, and the desired optical properties cannot be obtained.
[0180] Electron beam irradiation is usually performed in an inert gas, but can be performed in the air or under conditions where a small amount of oxygen is introduced if necessary. By appropriately introducing oxygen, oxygen barrier is generated in the optical layer that the electron beam contacts first, which can prevent damage to other optical layers and effectively allow the electron beam to irradiate only the adhesive.
[0181] In the case of ultraviolet curing type, the light irradiation intensity of the first active energy ray curable composition is not particularly limited, depending on the composition of the adhesive, but is preferably 10 mW / cm 2 Above and 1,000mW / cm 2 If the light irradiation intensity of the resin composition is less than 10 mW / cm 2 If the reaction time exceeds 1,000mW / cm 2 , the heat radiated from the light source and the heat released during the polymerization of the composition may cause yellowing of the constituent materials of the adhesive. It should be noted that the irradiation intensity is preferably an intensity in the wavelength region effective for the activation of the photocationic polymerization initiator (B), the photosensitizer (C), and the photosensitizer auxiliary (D), more preferably an intensity in the wavelength region below 400nm, and further preferably an intensity in the wavelength region above 280nm and below 320nm. Irradiation is performed once or multiple times with such light irradiation intensity, preferably to a value of 10mJ / cm 2 More preferably, 100 mJ / cm 2 Above and 1,000mJ / cm 2 The cumulative light intensity is set as follows. If the cumulative light intensity of the above adhesive is less than 10mJ / cm 2 On the other hand, if the cumulative light intensity exceeds 1,000 mJ / cm 2 At this time, the irradiation time becomes longer, which is not conducive to improving productivity. At this time, the cumulative light amount in which wavelength region (UVA (above 320nm and below 390nm), UVB (above 280nm and below 320nm) etc.) is required varies depending on the types of the first phase difference layer 13 and the second phase difference layer 30, the combination of the types of adhesives, etc.
[0182] The light source used in the present invention for polymerizing and curing the first active energy ray-curable composition by irradiation with active energy rays is not particularly limited, and examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in a wavelength range of 380 nm to 440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps. From the viewpoint of energy stability and simplicity of the device, an ultraviolet light source having a light emission distribution at a wavelength of 400 nm or less is preferred.
[0183] From the viewpoint of durability and adhesion, the first active energy ray-curable composition preferably satisfies the following formula (1).
[0184] (J A / J B )×100≥60(%) (1)
[0185] [Where J A It represents the heat amount (unit: mJ / g) measured by a differential scanning calorimeter when ultraviolet rays having a peak at a wavelength of 365 nm are irradiated to the first active energy ray-curable composition through a substrate having a light transmittance of 0% to 10% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm.
[0186] J B It represents the amount of heat (mJ / g) measured by a differential scanning calorimeter when ultraviolet rays having a peak at a wavelength of 365 nm are irradiated to the first active energy ray-curable composition without passing through the substrate.]
[0187] Heat J A and J B It can be measured according to the measurement method described in the Example column below.
[0188] By using the first active energy ray-curable composition satisfying formula (1), there is a tendency to easily obtain good water resistance and adhesion. In addition, the active energy ray-curable composition can be cured by irradiating active energy rays from the phase difference layer with low ultraviolet transmittance or the polarizing film 11 side, which was previously difficult.
[0189] The left side of formula (1) is 70% or more, more preferably 80% or more. The left side of formula (1) is usually 100% or less, for example, less than 100% or 90% or less.
[0190] The storage modulus of the first cured product layer 12 at 80° C. is, for example, 300 MPa or more, preferably 500 MPa or more, more preferably 900 MPa or more, and further preferably 1000 MPa or more from the viewpoint of preventing cracking during processing. The storage modulus at 80° C. can be measured by the measurement method described in the Examples section below.
[0191] (1st phase difference layer)
[0192] The first phase difference layer 13 is not particularly limited as long as it is a phase difference layer including at least one phase difference display layer that imparts a specified phase difference to light, and may be, for example, an optical compensation layer such as a 1 / 2 wavelength layer, a 1 / 4 wavelength layer, or a positive C plate. The phase difference layer may be a positive dispersion phase difference layer or a reverse wavelength dispersion phase difference layer. The first phase difference layer 13 may be a phase difference layer including at least one phase difference display layer, and may be formed only by a phase difference display layer, or may include a phase difference display layer and other layers at the same time. As other layers, for example, a substrate layer, an orientation film layer, a protective layer, and the like may be cited. It should be noted that other layers do not affect the value of the phase difference.
[0193] As the phase difference showing layer, a layer of a polymer containing a polymerizable liquid crystal compound (hereinafter, also referred to as a liquid crystal layer) or a stretched film can be cited. The first phase difference layer 13 preferably contains a liquid crystal layer with phase difference showing properties. In the case where the first phase difference layer 13 contains a liquid crystal layer, in the first phase difference layer 13, the surface on the side opposite to the first cured material layer 12 side is preferably a liquid crystal layer with phase difference showing properties. Compared with the case where the phase difference showing layer is a stretched film, the case where the phase difference showing layer is a liquid crystal layer is generally easier to thin film.
[0194] The light transmittance of the first phase difference layer 13 at a wavelength of 380nm can be 0% or more and 50% or less (preferably 0% or more and 10% or less), and the light transmittance at a wavelength of 400nm can be 30% or more. The light transmittance can be measured according to the measurement method described in the embodiment column described later. The light transmittance of the first phase difference layer 13 at a wavelength of 380nm can also be 0% or more and 5% or less, and the light transmittance at a wavelength of 400nm can also be 10% or more.
[0195] When the first retardation layer 13 is formed only of the retardation showing layer, the thickness is 0.5 μm or more and 10 μm or less, and preferably 0.5 μm or more and 5 μm or less.
[0196] When the first retardation layer 13 includes layers other than the retardation developing layer (substrate layer, alignment film layer, protective layer, etc.), the total thickness is 0.5 μm to 10 μm, more preferably 0.5 μm to 5 μm.
[0197] The half-wave layer imparts a phase difference of π (=λ / 2) to the electric field vibration direction (polarization plane) of incident light and has the function of changing the direction (polarization orientation) of linear polarization. In addition, if circularly polarized light is incident, the rotation direction of the circularly polarized light can be reversed.
[0198] The 1 / 2 wavelength layer is a layer in which Re(λ) as the in-plane retardation value at a specific wavelength λnm satisfies Re(λ)=λ / 2. Although Re(λ)=λ / 2 can be achieved at any wavelength in the visible light region, it is preferably achieved at a wavelength of 550nm. Re(550) as the in-plane retardation value at a wavelength of 550nm preferably satisfies 210nm≤Re(550)≤300nm. In addition, it is more preferable to satisfy 220nm≤Re(550)≤290nm.
[0199] The 1 / 4 wavelength layer imparts a phase difference of π / 2 (=λ / 4) to the electric field vibration direction (polarization plane) of incident light and has the function of converting linearly polarized light of a specific wavelength into circularly polarized light (or converting circularly polarized light into linearly polarized light).
[0200] The 1 / 4 wavelength layer is a layer in which Re(λ) as the in-plane retardation value at a specific wavelength λnm satisfies Re(λ)=λ / 4, and although it can be achieved at any wavelength in the visible light region, it is preferably achieved at a wavelength of 550nm. Re(550) as the in-plane retardation value at a wavelength of 550nm preferably satisfies 100nm≤Re(550)≤160nm. In addition, it is more preferable to satisfy 110nm≤Re(550)≤150nm.
[0201] As the optical compensation layer, for example, a positive A plate, a positive C plate, etc. can be cited. When the refractive index of the slow axis direction in the plane of the positive A plate is set to Nx, the refractive index of the fast axis direction in the plane is set to Ny, and the refractive index of the thickness direction is set to Nz, the relationship of Nx>Ny is satisfied. The positive A plate preferably satisfies the relationship of Nx>Ny≥Nz. In addition, the positive A plate can also function as a 1 / 4 wavelength layer. The positive C plate satisfies the relationship of Nz>Nx≥Ny.
[0202] The reverse wavelength dispersion refers to an optical property in which the in-plane retardation value at a short wavelength is smaller than the in-plane retardation value at a long wavelength, and preferably satisfies the following formula (b).
[0203] Re(450)≤Re(550)≤Re(650) (b)
[0204] It should be noted that Re(λ) represents the in-plane retardation value for light having a wavelength of λ nm.
[0205] The optical properties of the first retardation layer 13 can be adjusted by the alignment state of the liquid crystal compound constituting the retardation layer or the stretching method of the stretched film constituting the retardation layer.
[0206] (1) Phase difference display layer formed by liquid crystal layer
[0207] The case where the phase difference showing layer is a liquid crystal layer is described. Figure 2 2 is a schematic cross-sectional view schematically showing an example of a phase difference layer including a phase difference display layer as a liquid crystal layer and other layers. Figure 2 As shown in FIG. 1 , the phase difference layer 30 is formed by sequentially stacking a substrate layer 31, an orientation layer 32, and a phase difference display layer 33 as a liquid crystal layer. The phase difference layer is not limited to any structure as long as it includes the phase difference display layer 33 as a liquid crystal layer. Figure 2 The phase difference layer 30 shown can be a structure in which the substrate layer 31 is peeled off from the phase difference layer 30 and only the orientation layer 32 and the phase difference display layer 33 are formed, or it can be a structure in which the substrate layer 31 and the orientation layer 32 are peeled off from the phase difference layer 30 and only the phase difference display layer 33 as a liquid crystal layer is formed.
[0208] From the viewpoint of thinning, the phase difference layer is preferably a structure in which the base layer 31 is peeled off, and more preferably a structure formed of only the phase difference display layer 33 as a liquid crystal layer. The base layer 31 functions as a support layer for supporting the orientation layer 32 formed on the base layer 31 and the phase difference display layer 33 as a liquid crystal layer. The base layer 31 is preferably a film formed of a resin material.
[0209] As the resin material, for example, a resin material having excellent transparency, mechanical strength, thermal stability, and stretchability is used. Specifically, polyolefin resins such as polyethylene and polypropylene; cyclic polyolefin resins such as norbornene polymers; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; (meth) acrylic acid resins such as (meth) acrylic acid and poly(meth) methyl acrylate; cellulose ester resins such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; vinyl alcohol resins such as polyvinyl alcohol and polyvinyl acetate; polycarbonate resins; polystyrene resins; polyarylate resins; polysulfone resins; polyethersulfone resins; polyamide resins; polyimide resins; polyetherketone resins; polyphenylene sulfide resins; polyphenylene ether resins, and mixtures and copolymers thereof are preferably used among these resins. Any one of cyclic polyolefin resins, polyester resins, cellulose ester resins, and (meth) acrylic resins or mixtures thereof is preferably used. In addition, the above-mentioned "(meth)acrylic acid" means "at least one of acrylic acid and methacrylic acid".
[0210] The base material layer 31 may be a single layer of one or a mixture of two or more of the above resins, or may have a multilayer structure of two or more layers. In the case of a multilayer structure, the resins constituting each layer may be the same or different.
[0211] Any additives may be added to the resin material constituting the resin film, and examples of the additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0212] The thickness of the base layer 31 is not particularly limited, but in order to make the entire thickness of the first retardation layer 13 10 μm or less, it is preferable that the base layer 31 is not included.
[0213] In order to improve the adhesion between the substrate layer 31 and the orientation layer 32, at least the surface of the substrate layer 31 on the side where the orientation layer 32 is formed may be subjected to corona treatment, plasma treatment, flame treatment, etc., or a primer layer may be formed. It should be noted that when the substrate layer 31, or the substrate layer 31 and the orientation layer 32 are peeled off to form a phase difference layer, the peeling may be facilitated by adjusting the adhesion at the peeling interface.
[0214] The orientation layer 32 has an orientation restriction force that allows the liquid crystal compound contained in the phase difference display layer 33 as the liquid crystal layer formed on the orientation layer 32 to be oriented in the desired direction. As the orientation layer 32, an orientation polymer layer formed of an orientation polymer, a photo-orientation polymer layer formed of a photo-orientation polymer, and a groove orientation layer having a concave-convex pattern and a plurality of grooves on the surface of the layer can be cited. The thickness of the orientation layer 32 is usually 0.01 μm or more and 10 μm or less, preferably 0.01 μm or more and 5 μm or less.
[0215] The composition in which the oriented polymer is dissolved in the solvent is applied to the base material layer 31 and the solvent is removed, and a rubbing treatment is performed as needed to form an oriented polymer layer. In this case, the orientation restriction force can be arbitrarily adjusted in the oriented polymer layer formed by the oriented polymer by the surface state of the oriented polymer and the rubbing conditions.
[0216] The photo-aligned polymer layer can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to the base layer 31 and irradiating the substrate with polarized light. In this case, the alignment restraining force in the photo-aligned polymer layer can be arbitrarily adjusted by, for example, irradiating the photo-aligned polymer with polarized light.
[0217] The groove orientation layer can be formed, for example, by the following methods: a method of exposing and developing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape to form a concave-convex pattern; a method of forming an uncured layer of an active energy ray-curable resin on a plate-shaped original disk having grooves on the surface, transferring the layer to a substrate layer 31 and curing it; a method of forming an uncured layer of an active energy ray-curable resin on a substrate layer 31, and forming the concave-convex by pressing a roller-shaped original disk having the concave-convex onto the layer, etc., and then curing it.
[0218] The phase difference display layer 33 as a liquid crystal layer is not particularly limited as long as it is a layer that imparts a specified phase difference to light. For example, it can be a layer that functions as a phase difference display layer for a 1 / 2 wavelength layer, a phase difference display layer for a 1 / 4 wavelength layer, a phase difference display layer for an optical compensation layer such as a positive C plate, and a phase difference display layer for a 1 / 4 wavelength layer with reverse wavelength dispersion.
[0219] The phase difference display layer 33 as a liquid crystal layer can be formed using a known liquid crystal compound.
[0220] The type of liquid crystal compound is not particularly limited, and rod-shaped liquid crystal compounds, disc-shaped liquid crystal compounds, and mixtures thereof may be used. In addition, the liquid crystal compound may be a polymeric liquid crystal compound, a polymerizable liquid crystal compound, or a mixture thereof. As the liquid crystal compound, for example, there can be mentioned liquid crystal compounds described in JP-A-11-513019, JP-A-2005-289980, JP-A-2007-108732, JP-A-2010-244038, JP-A-2010-31223, JP-A-2010-270108, JP-A-2011-6360, JP-A-2011-207765, JP-A-2016-81035, International Publication No. 2017 / 043438, and JP-A-2011-207765.
[0221] For example, when a polymerizable liquid crystal compound is used, a composition containing the polymerizable liquid crystal compound is applied on the alignment layer 32 to form a coating film, and the coating film is cured to form the phase difference display layer 33. The thickness of the phase difference display layer 33 is preferably 0.5 μm to 10 μm, and more preferably 0.5 μm to 5 μm.
[0222] The composition containing the polymerizable liquid crystal compound may further contain a polymerization initiator, a polymerizable monomer, a surfactant, a solvent, a close fit improver, a plasticizer, an alignment agent, etc. in addition to the liquid crystal compound. As a coating method for the composition containing the polymerizable liquid crystal compound, a well-known method such as a die coating method can be cited. As a curing method for the composition containing the polymerizable liquid crystal compound, a well-known method such as irradiation with active energy rays (such as ultraviolet rays) can be cited.
[0223] (2) Phase difference layer having a stretched film as a phase difference showing layer
[0224] The case where the phase difference display layer is a stretched film is described. The stretched film is usually obtained by stretching a substrate. As a method for stretching the substrate, for example, a roll (winding body) in which the substrate is wound in a roll shape is prepared, the substrate is continuously rolled out from the winding body, and the rolled-out substrate is transported to a heating furnace. The set temperature of the heating furnace is set to a range of near the glass transition temperature of the substrate (°C) to [glass transition temperature + 100] (°C), preferably set to a range of near the glass transition temperature (°C) to [glass transition temperature + 50] (°C). In the heating furnace, when stretching in the traveling direction of the substrate or in a direction orthogonal to the traveling direction, the conveying direction and tension are adjusted to perform uniaxial or biaxial heat stretching treatment at an angle of any angle. The stretching ratio is usually 1.1 to 6 times, preferably 1.1 to 3.5 times.
[0225] In addition, as a method for stretching in an oblique direction, as long as it is a method that can continuously tilt the orientation axis along a desired angle, there is no particular limitation, and a known stretching method can be adopted. Such a stretching method can be cited, for example, the method described in Japanese Patent Laid-Open No. 50-83482 and Japanese Patent Laid-Open No. 2-113920. In the case of imparting phase difference to the film by stretching, the thickness after stretching is determined according to the thickness before stretching and the stretching ratio.
[0226] The above-mentioned substrate is usually a transparent substrate. A transparent substrate means a substrate having transparency that can transmit light, especially visible light, and transparency refers to the property that the transmittance for light with a wavelength of more than 380nm and less than 780nm is 80% or more. As a specific transparent substrate, a translucent resin substrate can be cited. As resins constituting the translucent resin substrate, polyolefins such as polyethylene and polypropylene; cyclic olefin resins such as norbornene polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene ether. From the viewpoint of ease of acquisition and transparency, polyethylene terephthalate, polymethacrylate, cellulose ester, cyclic olefin resin or polycarbonate is preferred.
[0227] Cellulose ester is a substance in which a part or all of the hydroxyl groups contained in cellulose are esterified, and it can be easily obtained from the market. In addition, cellulose ester substrates can also be easily obtained from the market. Examples of commercially available cellulose ester substrates include "FUJITAC (registered trademark) Film" (Fuji Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (Konica Minolta Opto Co., Ltd.), etc.
[0228] Polymethacrylate and polyacrylate (hereinafter, polymethacrylate and polyacrylate may be collectively referred to as (meth)acrylic resin) are easily available from the market.
[0229] As the (meth)acrylic resin, for example, homopolymers of alkyl methacrylate or alkyl acrylate, copolymers of alkyl methacrylate and alkyl acrylate, etc. can be cited. As the alkyl methacrylate, specifically, methyl methacrylate, ethyl methacrylate, propyl methacrylate, etc. can be cited. In addition, as the alkyl acrylate, specifically, methyl acrylate, ethyl acrylate, propyl acrylate, etc. can be cited. The (meth)acrylic resin can use a resin sold as a general-purpose (meth)acrylic resin. As the (meth)acrylic resin, a resin called an impact-resistant (meth)acrylic resin can also be used.
[0230] In order to further improve the mechanical strength, it is also preferred that the (meth) acrylic resin contains rubber particles. The rubber particles are preferably acrylic rubber particles. Here, the so-called acrylic rubber particles are particles with rubber elasticity obtained by polymerizing acrylic monomers with acrylic acid alkyl esters such as butyl acrylate and 2-ethylhexyl acrylate as the main component in the presence of a multifunctional monomer. The acrylic rubber particles can be a material in which such particles with rubber elasticity are formed in a single layer, or can be a multilayer structure having at least one rubber elastic layer. As acrylic rubber particles with a multilayer structure, there can be cited: particles having the above-mentioned rubber elastic particles as the core and the periphery thereof covered with a hard methacrylate alkyl ester polymer; particles having the hard methacrylate alkyl ester polymer as the core and the periphery thereof covered with the above-mentioned rubber elastic acrylic polymer; and particles having the periphery of the hard core covered with a rubber elastic acrylic polymer and the periphery thereof covered with a hard methacrylate alkyl ester polymer, etc. The rubber particles forming the elastic layer generally have an average diameter in the range of 50 nm to 400 nm.
[0231] The content of rubber particles in the (meth)acrylic resin is usually 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the (meth)acrylic resin. The (meth)acrylic resin and the acrylic rubber particles are sold in a mixed state, so commercial products thereof can be used. Examples of commercial products of (meth)acrylic resins with acrylic rubber particles include "HT55X" and "TECHNOLLOY S001" sold by Sumitomo Chemical Co., Ltd. "TECHNOLLOY S001" is sold in the form of a film.
[0232] Cyclic olefin resins can be easily obtained from the market. Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) [Ticona (Germany)], "Arton" (registered trademark) [JSR (Strain)], "ZEONOR" (registered trademark) [Japan ZEON (Strain)], "ZEONEX" (registered trademark) [Japan ZEON (Strain)] and "APEL" (registered trademark) [Mitsui Chemicals (Strain)]. Such cyclic olefin resins can be made into films by well-known methods such as solvent casting and melt extrusion to form a substrate. In addition, commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include "ESCENA" (registered trademark) [Sekisui Chemical (Strain)], "SCA40" (registered trademark) [Sekisui Chemical (Strain)], "ZEONOR Film" (registered trademark) [OPTES (Strain)] and "Arton Film" (registered trademark) [JSR (Strain)].
[0233] In the case where the cyclic olefin resin is a copolymer of a cyclic olefin and a chain olefin and an aromatic compound having a vinyl group, the content ratio of the structural unit derived from the cyclic olefin is generally 50 mol% or less relative to the total structural units of the copolymer, preferably in the range of 15 mol% or more and 50 mol% or less. As chain olefins, ethylene and propylene can be cited, and as aromatic compounds having a vinyl group, styrene, α-methylstyrene and alkyl-substituted styrene can be cited. In the case where the cyclic olefin resin is a terpolymer of a cyclic olefin and a chain olefin and an aromatic compound having a vinyl group, the content ratio of the structural unit derived from the chain olefin is generally 5 mol% or more and 80 mol% or less relative to the total structural units of the copolymer, and the content ratio of the structural unit derived from the aromatic compound having a vinyl group is generally 5 mol% or more and 80 mol% or less relative to the total structural units of the copolymer. Such a terpolymer has the advantage that the amount of expensive cyclic olefins used can be reduced in its manufacture.
[0234] (Other layers)
[0235] The laminate 100 may include other layers in addition to the polarizing film 11, the first cured material layer 12, and the first retardation layer 13. Figure 3 The other layers are described below. Figure 3 As shown, in the laminate 100, the second cured layer 14 and the second phase difference layer 15 may be sequentially laminated on the side of the first phase difference layer 13 opposite to the first cured layer 12. In addition, in the laminate 100, a thermoplastic resin film 16 may be laminated on the side of the polarizing film 11 opposite to the first cured layer 12 via an adhesive layer 17. In addition, in the laminate 100, an adhesive layer 18 may be provided on the side of the second phase difference layer 15.
[0236] (Second Cured Material Layer)
[0237] The second cured material layer 14 is disposed between the first retardation layer 13 and the second retardation layer 15, and bonds the first retardation layer 13 and the second retardation layer 15. The second cured material layer 14 includes a cured material of the second active energy ray-curable composition.
[0238] The second active energy ray-curable composition may be any composition that is cured by irradiating active energy rays, and may be, for example, a cationically polymerizable adhesive composition or a radically polymerizable adhesive composition. The second active energy ray-curable composition may not contain any of a photosensitizer and a photosensitizer. As examples and preferred ranges of the cationically polymerizable adhesive composition, for example, the examples and preferred ranges in the description of the first active energy ray-curable composition may be applied.
[0239] The thickness of the second cured material layer 14 is, for example, 20 μm or less, preferably 10 μm or less, more preferably 6 μm or less, and further preferably 5 μm or less. The thickness of the second cured material layer 14 is, for example, 0.5 μm or more, and preferably 1 μm or more.
[0240] (Second phase difference layer)
[0241] The second phase difference layer 15 is not particularly limited as long as it is a phase difference layer including at least one phase difference display layer that imparts a predetermined phase difference to light. The examples and preferred ranges of the second phase difference layer 15 can be applied to the examples and preferred ranges of the first phase difference layer 13. Hereinafter, the laminated body obtained by bonding the second phase difference layer 15 and the first phase difference layer 13 via the second cured material layer 14 is also referred to as a phase difference layer laminated body.
[0242] The second phase difference layer 15 preferably includes a phase difference-visible liquid crystal layer. When the second phase difference layer includes a liquid crystal layer, the surface of the second phase difference layer 15 on the second cured material layer 14 side is preferably a phase difference-visible liquid crystal layer. When the laminate includes the first phase difference layer and the second phase difference layer, at least one of the first phase difference layer and the second phase difference layer preferably includes a phase difference-visible liquid crystal layer.
[0243] The second retardation layer 15 may have a light transmittance of 0% to 90% at a wavelength of 380nm, and a light transmittance of 30% to 400nm. The second retardation layer 15 may have a light transmittance of 0% to 80% at a wavelength of 380nm, and a light transmittance of 50% to 400nm.
[0244] When the laminate includes the first retardation layer and the second retardation layer, at least one of the first retardation layer and the second retardation layer preferably has a light transmittance of 0% to 10% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm.
[0245] The thickness of the second retardation layer 15 is preferably 0.5 μm or more and 50 μm or less, and more preferably 0.5 μm or more and 5 μm or less.
[0246] As a combination of the first retardation layer 13 and the second retardation layer 15, the following combinations are mentioned, for example:
[0247] i) Combination of 1 / 2 wavelength layer and 1 / 4 wavelength layer,
[0248] ii) Combination of 1 / 2 wavelength layer and optical compensation layer,
[0249] iii) Combination of a 1 / 4 wavelength layer and an optical compensation layer.
[0250] In the case of i), it is preferred that the first retardation layer 13 is a half-wavelength layer, and the second retardation layer 15 is a quarter-wavelength layer.
[0251] In case ii), the first retardation layer 13 is preferably a half wavelength layer and the second retardation layer 15 is an optical compensation layer, and more preferably the first retardation layer 13 is a half wavelength layer and the second retardation layer 15 is a positive C plate.
[0252] In the case of iii), the first retardation layer 13 is preferably a quarter wavelength layer and the second retardation layer 15 is an optical compensation layer, and more preferably the first retardation layer 13 is a quarter wavelength layer and the second retardation layer 15 is a positive C plate.
[0253] (Thermoplastic resin film)
[0254] The thermoplastic resin film 16 may be disposed on the viewing side of the laminate. The thermoplastic resin film 16 may have the function of a protective film for protecting the polarizing film 11. The laminate obtained by laminating the polarizing film 11 and the thermoplastic resin film 16 via the adhesive layer 17 is also called a linear polarizing plate. Although not shown, the thermoplastic resin film may also be disposed on both sides of the polarizer. The thermoplastic resin film is preferably disposed on one side of the polarizer, and is more preferably disposed only on the viewing side of the laminate from the viewpoint of thinning.
[0255] The material of the thermoplastic resin film 16 is not particularly limited, and examples thereof include cyclic polyolefin resin films, cellulose acetate resin films containing resins such as triacetyl cellulose and diacetyl cellulose, polyester resin films containing resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polycarbonate resin films, (meth) acrylic resin films, and polypropylene resin films, which are known in the art. From the viewpoint of thinning, the thickness of the thermoplastic resin film 16 is usually 300 μm or less, preferably 200 μm or less, and more preferably 50 μm or less, and is usually 5 μm or more, and preferably 10 μm or more. In addition, the thermoplastic resin film 16 may have a phase difference, or may not have a phase difference.
[0256] If necessary, the thermoplastic resin film 16 may contain one or more additives such as rubber particles, lubricants, fluorescent whitening agents, dispersants, heat stabilizers, light stabilizers, ultraviolet absorbers, infrared absorbers, antistatic agents, antioxidants, etc.
[0257] (Adhesive layer)
[0258] In order to bond the thermoplastic resin film 16 to the polarizing film 11, an adhesive layer 17 may be provided. The adhesive layer 17 preferably includes a cured product of a water-based adhesive composition. The water-based adhesive composition may be, for example, a composition using a polyvinyl alcohol resin or a urethane resin as a main component and blending a crosslinking agent or a curing compound such as an isocyanate compound or an epoxy compound to improve adhesion.
[0259] When a polyvinyl alcohol resin is used as the main component of the water-based adhesive composition, in addition to partially saponified polyvinyl alcohol and completely saponified polyvinyl alcohol, modified polyvinyl alcohol resins such as carboxyl-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, hydroxymethyl-modified polyvinyl alcohol, and amino-modified polyvinyl alcohol can also be used. The water-based adhesive composition preferably contains acetoacetyl-modified polyvinyl alcohol. Such an aqueous solution of a polyvinyl alcohol resin is used as a water-based adhesive, and the concentration of the polyvinyl alcohol resin in the water-based adhesive is usually 1 mass part or more and 10 mass parts or less relative to 100 mass parts of water, preferably 1 mass part or more and 5 mass parts or less.
[0260] In the water-based adhesive composition composed of the aqueous solution of the polyvinyl alcohol resin, in order to improve the adhesion, a curable compound such as a polyaldehyde, a water-soluble epoxy resin, a melamine compound, a zirconium oxide compound, and a zinc compound can be mixed. If an example of a water-soluble epoxy resin is given, there is: a water-soluble polyamide epoxy resin obtained by reacting a polyalkylene polyamine such as diethylenetriamine or triethylenetetramine with a dicarboxylic acid such as adipic acid, and reacting epichlorohydrin with the polyamide polyamine. As a commercial product of such a polyamide epoxy resin, there are: "Sumirez Resin 650" and "Sumirez Resin 675" sold by Sumika ChemteX Co., Ltd., "WS-525" sold by Japan PMC Co., Ltd., etc. In the case of mixing a water-soluble epoxy resin, its addition amount is usually 1 mass part or more and 100 mass parts or less relative to 100 mass parts of the polyvinyl alcohol resin, preferably 1 mass part or more and 50 mass parts or less.
[0261] In addition, when using carbamate resin as the main component of the water-based adhesive composition, it is effective to set the polyester ionomer carbamate resin as the main component of the water-based adhesive composition. The polyester ionomer carbamate resin mentioned here refers to a carbamate resin with a polyester skeleton obtained by introducing a small amount of ionic components (hydrophilic components). The ionomer carbamate resin is directly emulsified in water without using an emulsifier to form an emulsion, so it can be made into a water-based adhesive. When using a polyester ionomer carbamate resin, it is effective to use a water-soluble epoxy compound as a crosslinking agent. The practice of setting the polyester ionomer carbamate resin as an adhesive for polarizing plates is recorded in Japanese Patent Publication No. 2005-70140 and Japanese Patent Publication No. 2005-208456.
[0262] The water-based adhesive composition may contain an ultraviolet absorber, a filler, a flow regulator, a defoamer, a leveling agent, a pigment, an organic solvent, and the like.
[0263] The water-based adhesive composition is usually used in the form of each component dissolved in water. The components insoluble in water contained in the water-based adhesive composition can be dispersed in the system. The water-based adhesive composition is applied to one side of the polarizer and dried to form a transparent adhesive.
[0264] The water-based adhesive composition can be applied to one or both surfaces of a polarizer or a thermoplastic resin film and laminated, and then heated to evaporate water vapor and cause a thermal crosslinking reaction, thereby sufficiently bonding the two.
[0265] The thickness of the adhesive layer 17 is, for example, 20 μm or less, preferably 10 μm or less, and more preferably 5 μm or less. The thickness of the adhesive layer 17 can be, for example, 0.1 μm or more.
[0266] (Adhesive layer)
[0267] The laminate 100 may have an adhesive layer 18 on the side of the second phase difference layer 15. The adhesive layer 18 may be composed of an adhesive composition having a resin such as (meth) acrylic acid, rubber, urethane, ester, silicone, or polyvinyl ether as a main component. Among them, an adhesive composition having a (meth) acrylic resin as a base polymer having excellent transparency, weather resistance, heat resistance, etc. is preferred. The adhesive composition may be an active energy ray-curable type or a thermosetting type. The thickness of the adhesive layer 18 is generally 3 μm or more and 30 μm or less, preferably 3 μm or more and 25 μm or less.
[0268] As the (meth)acrylic resin (base polymer) used in the adhesive composition, for example, it is preferred to use a polymer or copolymer using one or more of (meth)acrylates such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate as monomers. It is preferred to copolymerize a polar monomer with the base polymer. As the polar monomer, for example, monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate can be cited.
[0269] The adhesive composition may only contain the above-mentioned base polymer, but usually also contains a crosslinking agent. Examples of the crosslinking agent include: a crosslinking agent that forms a carboxylic acid metal salt with a divalent or higher metal ion and a crosslinking agent that forms an amide bond with a carboxyl group; a crosslinking agent that forms an ester bond with a polyepoxide or polyol and a crosslinking agent that forms an amide bond with a carboxyl group; and a crosslinking agent that forms an amide bond with a polyisocyanate compound and a carboxyl group. Among them, a polyisocyanate compound is preferred.
[0270] (Method for producing laminated body)
[0271] For an example of the method for producing the laminate of the present invention, refer to Figure 4 For explanation. Figure 4 As shown in (A), a linear polarizing plate 10 is prepared by laminating a polarizing film 11 and a thermoplastic resin film 16 via an adhesive layer 17. Figure 4 As shown in (B), a first phase difference layer 13 including a first phase difference showing layer 21, a first orientation layer 22 and a first substrate layer 23, and a second phase difference layer 15 including a second phase difference showing layer 26, a second orientation layer 25 and a second substrate layer 24 are prepared. Figure 4 As shown in (C), the first phase difference layer 13 and the second phase difference layer 15 are stacked with the second cured layer 14 interposed therebetween to produce a phase difference layer stack 50 in which the first substrate layer 23, the first orientation layer 22, the first phase difference display layer 21, the second cured layer 14, the second phase difference display layer 26, the second orientation layer 25, and the second substrate layer 24 are stacked in sequence. Figure 4 As shown in (D), the polarizing film 11 side of the linear polarizing plate 10 and the first retardation layer 13 side of the retardation layer stack 50 are stacked with the first cured material layer 12 interposed therebetween to obtain a stack 70 .
[0272] As a method for bonding the polarizing film 11 to the thermoplastic resin film 16, the following method can be cited: applying a water-based adhesive composition to either or both of the bonding surfaces of the polarizing film 11 or the thermoplastic resin film 16, laminating one on the bonding surface of the other, and curing the water-based adhesive composition constituting the adhesive layer 17.
[0273] As a method for bonding the first phase difference layer 13 and the second phase difference layer 15, the following method can be cited: an active energy ray-curable composition is applied to either or both of the bonding surface of the first phase difference layer 13 and the bonding surface of the second phase difference layer 15, one is laminated on the bonding surface of the other, and an active energy ray-curable adhesive constituting the second cured layer 14 is cured. The active energy ray for curing the second cured layer 14 can be irradiated from either side of the first phase difference layer 13 and the second phase difference layer 15, or from both sides.
[0274] As a method for bonding the linear polarizing plate 10 and the phase difference layer laminate 50, the following method can be cited: an active energy ray-curable composition is applied to either or both of the bonding surface of the linear polarizing plate 10 or the bonding surface of the phase difference layer laminate 50, and the bonding surface of the other is laminated to one, and the active energy ray-curable adhesive constituting the first cured product layer 12 is cured. From the viewpoint of adhesion, it is preferred to apply the active energy ray-curable adhesive composition only to the bonding surface of the phase difference layer laminate 50. The active energy ray for curing the first cured product layer 12 can be irradiated from either side of the linear polarizing plate 10 and the phase difference layer laminate 50, or from both sides.
[0275] Either or both of the laminating surfaces may be subjected to corona treatment, plasma treatment, etc., or a primer layer may be formed. When the water-based adhesive composition and the active energy ray-curable composition are applied, various coating methods such as a doctor blade, a wire rod, a die coater, a comma coater, a gravure coater, etc. may be used.
[0276] The laminate of the present invention may be Figure 4 (D) The laminated body shown in the figure may be a laminated body obtained by peeling off at least one of the first substrate layer 23 and the second substrate layer 24. Figure 4 The laminate shown in (D) may be a laminate obtained by peeling off the first substrate layer 23 and the first orientation layer 22, or may be a laminate obtained by peeling off the first substrate layer 23 and the first orientation layer 22. Figure 4 The laminate shown in (D) is a laminate obtained by peeling the second base layer 24 and the second orientation layer 25 .
[0277] (use)
[0278] The laminate can be used for an image display device. An image display device refers to a device having an image display panel, and includes a light-emitting element or a light-emitting device as a light source. As an image display device, a liquid crystal display device, an organic electroluminescent (EL) display device, an inorganic electroluminescent (EL) display device, a touch panel display device, an electron emission display device (such as a field emission display device (FED), a surface electric field emission display device (SED)), an electronic paper (a display device using electronic ink and an electrophoretic element), a plasma display device, a projection type display device (such as a grating light valve (GLV) display device, a display device with a digital micromirror device (DMD)) and a piezoelectric ceramic display, etc. The liquid crystal display device also includes any one of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device and a projection type liquid crystal display device. These image display devices can be image display devices that display two-dimensional images, or they can be stereoscopic image display devices that display three-dimensional images. In particular, the polarizing plate composite which is a circular polarizing plate can be effectively used in an organic electroluminescent (EL) display device which can include an image display panel having a curved portion.
[0279] The laminate can function as a circular polarizing plate or an anti-reflection film. The laminate can be arranged on the viewing side of the image display layer panel with the polarizing film on the viewing side. The laminate is preferably used as a circular polarizing plate or an anti-reflection film for an in-vehicle image display device.
[0280] Example
[0281] Hereinafter, the present invention will be described in more detail with reference to Examples. "%" and "parts" in the Examples are by mass % and by mass parts unless otherwise specified.
[0282] (Viscosity measurement)
[0283] The active energy ray-curable composition was temperature-controlled to 25° C. using an E-type viscometer [“TVE-25” manufactured by Toki Sangyo Co., Ltd.] and then measured at 10 rpm.
[0284] (Calometry)
[0285] The active energy ray-curable adhesive composition was placed in a differential scanning calorimeter, and ultraviolet rays having a peak at a wavelength of 365 nm were irradiated to the active energy ray-curable adhesive composition to measure the calorimetric value. B (Unit: mJ / g). The active energy ray-curable adhesive composition is irradiated with ultraviolet rays having a peak at a wavelength of 365 nm through a substrate having a light transmittance of 0% to 10% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm, and the heat J is measured. A(Unit: mJ / g).
[0286] (Light transmittance measurement)
[0287] The λ / 4 retardation layer and the positive C plate were cut into a size of 30 mm×30 mm, and the transmittance was measured between wavelengths of 200 and 510 nm. The measurement was performed using an ultraviolet visible spectrophotometer “UV-2450” manufactured by Shimadzu Corporation.
[0288] (Determination of storage modulus at 80°C)
[0289] The prepared active energy ray-curable composition was applied to one side of a polyethylene terephthalate film (trade name "TOYOBOESTERFILM E7002", manufactured by Toyobo Co., Ltd.) using a coater (bar coater, manufactured by Daiichi Rika Co., Ltd.) so that the film thickness after curing was about 10 μm. Then, the film was irradiated with a "D Bulb" manufactured by Fusion UV Systems at a cumulative light dose of 1,000 mJ / cm 2 The adhesive was cured by irradiating ultraviolet rays in a manner. It was cut into a size of 5 mm × 30 mm, and the polyethylene terephthalate film was peeled off to obtain a cured film of the adhesive. The cured film thus obtained was held with a clamp interval of 2 cm using a dynamic viscoelasticity measuring device "DVA-220" manufactured by IT Measurement Control Co., Ltd. in a manner such that its long side became the stretching direction, and the frequency of stretching and shrinking was set to 1 Hz, and the heating rate was set to 3°C / min, and the storage modulus at a temperature of 80°C was obtained.
[0290] (Adhesion test)
[0291] An acrylic adhesive (film thickness 25 μm) was bonded to the C-plate side of the laminated bodies produced in Examples and Comparative Examples, and the laminated bodies were cut into a size of 200 mm in length×25 mm in width, and then the adhesive layer was bonded to a soda glass substrate.
[0292] Next, insert the blade of a cutting knife between the polarizing plate and the λ / 4 phase difference layer, peel off 30 mm from the end in the length direction, and clamp the peeled portion with the clamp part of a universal tensile testing machine [(co., Ltd.) Shimadzu Corporation "AG-1"]. For the test piece in this state, in an atmosphere of temperature 23°C and relative humidity 55%, according to JIS K 6854-2: 1999 "Adhesive-Peel Adhesion Strength Test Method-Part 2: 180-degree peeling", a 180-degree peeling test is carried out at a clamp moving speed of 300 mm / min, and the average peeling force of the length of 170 mm excluding the 30 mm of the clamp part is obtained, and evaluated based on the following criteria. The results are shown in Table 1.
[0293] ○: 180° peeling force is 0.5N or more
[0294] ×: 180° peeling force is less than 0.5N
[0295] (Durability Evaluation)
[0296] The laminates prepared in the examples and comparative examples were cut into a size of 30 mm × 30 mm and subjected to a wet heat test in a wet heat environment at a temperature of 80°C and a relative humidity of 90% for 24 hours. The polarization degree and phase difference before and after the test were measured and the absolute value of the difference was obtained. Evaluation was performed based on the following criteria.
[0297] Polarization degree benchmark:
[0298] ◎: 1.0 or less
[0299] ○: more than 1.0 and less than 3.0
[0300] ×: more than 3.0
[0301] Benchmarks for in-plane delay values:
[0302] ◎: 0.5 or less
[0303] ○: more than 0.5 and less than 1.0
[0304] ×: more than 1.0
[0305] In the measurement of polarization degree, an ultraviolet visible spectrophotometer "UV-2450" manufactured by Shimadzu Corporation is used, which is equipped with a "film holder with polarizer" as an optional accessory. The transmission spectrum in the transmission axis direction and the absorption axis direction of the polarizer in the wavelength range of 380nm to 780nm is obtained, and the polarization degree is calculated based on the "UV-Probe" software attached to the spectrophotometer.
[0306] The in-plane retardation value was measured using a phase difference measuring device "KOBRA-WR" manufactured by Oji Scientific Instruments Co., Ltd., and the in-plane retardation value R at a wavelength of 550 nm was obtained. e .
[0307] The in-plane retardation value Re is defined by the following formula.
[0308] R e =(n x -n y )×d
[0309] The refractive index in the slow axis direction in the plane (the direction in which the refractive index becomes the maximum in the plane) is n x The refractive index in the in-plane fast axis direction (the direction perpendicular to the in-plane slow axis direction) is set to n y , the thickness of the laminate is set to d. )
[0310] (Preparation of the first active energy ray-curable composition)
[0311] The components shown in Table 1 were mixed in the proportions shown in Table 1 (parts by mass) and degassed to prepare the first active energy ray-curable composition (adhesives 1 to 13). It should be noted that the cationic polymerization initiator (B-1) was blended in the form of a 50% propylene carbonate solution, and Table 1 shows the solid content thereof. The viscosity measurement results and the calorimetric measurement results are shown in Table 2.
[0312] [Table 1]
[0313]
[0314] (Cationically polymerizable compound (A))
[0315] A-1: 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (trade name: OXT-221, manufactured by Toagosei Co., Ltd., viscosity 0.012 Pa·s (temperature 25° C.), refractive index 1.45 (wavelength 589 nm))
[0316] A-2: 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation, viscosity 0.25 Pa·s (temperature 25° C.), refractive index 1.50 (wavelength 589 nm))
[0317] A-3: 1,2-epoxy-4-(2-epoxyethyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (trade name: EHPE3150, manufactured by Daicel Corporation, viscosity exceeding 30 Pa·s (temperature 25° C.), refractive index 1.54 (wavelength 589 nm))
[0318] A-4: Neopentyl glycol diglycidyl ether (trade name: EX-211L, manufactured by Nagase ChemteX Co., Ltd., viscosity 0.02 Pa·s (temperature 25° C.), refractive index 1.45 (wavelength 589 nm))
[0319] A-5: 2-ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Co., Ltd., viscosity 0.004 Pa·s (temperature 25° C.), refractive index 1.43 (wavelength 589 nm))
[0320] A-6: bisphenol A type epoxy resin (trade name: jER828, manufactured by Mitsubishi Chemical Corporation, viscosity 13 Pa·s (temperature 25° C.), refractive index 1.57 (wavelength 589 nm))
[0321] A-7: xylylenebisoxetane (trade name: OXT-121, manufactured by Toa Gosei Co., Ltd., viscosity 0.15 Pa·s (temperature 25°C), refractive index 1.51 (wavelength 589 nm))
[0322] (Photocationic polymerization initiator (B))
[0323] B-1: CPI-100P (manufactured by San-Apro Co., Ltd., 50 mass % solution)
[0324] (Photosensitizer (C))
[0325] C-1: 9,10-Dibutoxyanthracene
[0326] (Photosensitizer (D))
[0327] D-1: 1,4-Diethoxynaphthalene
[0328] [Table 2]
[0329]
[0330] (Second active energy ray-curable composition)
[0331] 70 parts by mass of 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation), 20 parts by mass of neopentyl glycol diglycidyl ether (trade name: EX-211L, manufactured by Nagase ChemteX Corporation), 10 parts by mass of 2-ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX Corporation), 2.25 parts by mass of a cationic polymerization initiator (trade name: CPI-100P, manufactured by San-Apro Corporation) in terms of solid content, and 2 parts by mass of 1,4-diethoxynaphthalene were mixed and degassed to prepare a second active energy ray-curable composition.
[0332] (Acrylic adhesive sheet A)
[0333] (1) Material preparation
[0334] The acrylic base polymer (H-1), isocyanate crosslinking agent (H-2), and silane coupling agent (H-3) shown below were prepared.
[0335] (H-1) Copolymer of butyl acrylate, methyl acrylate, acrylic acid and hydroxyethyl acrylate
[0336] (H-2) Ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate (solid content concentration 75%) ("Coronate L" (trade name), manufactured by Tosoh Corporation)
[0337] (H-3) 3-Glycidoxypropyltrimethoxysilane, liquid ("KBM-403" (trade name), manufactured by Shin-Etsu Chemical Co., Ltd.)
[0338] (2) Preparation of Adhesive 1
[0339] 100 parts by mass of the acrylic base polymer (H-1), 0.2 parts by mass of an isocyanate crosslinking agent (H-2), and 0.2 parts by mass of a silane coupling agent (H-3) were mixed, stirred sufficiently, and diluted with ethyl acetate to prepare an adhesive 1.
[0340] (3) Preparation of Acrylic Adhesive Sheet A
[0341] The adhesive 1 prepared above was applied on a release paper and heated at 90° C. for 1 minute to obtain an acrylic adhesive sheet A. The obtained adhesive layer was peeled off from the release paper and the thickness was measured, which was 5 μm. The thickness of the adhesive layer was measured using a contact film thickness meter [trade name "DIGIMICRO MH-15M" manufactured by Nikon Corporation].
[0342] (Acrylic adhesive sheet B)
[0343] Adhesive 1 for preparing acrylic adhesive sheet A was applied onto release paper so that the adhesive layer had a thickness of 25 μm, and then heat-treated at 90° C. for 1 minute to obtain acrylic adhesive sheet B.
[0344] (Production of Linear Polarization Plate)
[0345] A polyvinyl alcohol film with a thickness of 20 μm, a degree of polymerization of 2,400, and a saponification degree of 99.9% or more was uniaxially stretched at a stretching ratio of 4.5 times on a roller heated to 125°C, and then immersed in 28°C water for 30 seconds while maintaining a tight state, and then immersed in a 28°C dyeing bath containing 0.05 parts by mass of iodine and 5 parts by mass of potassium iodide per 100 parts by mass of water for 30 seconds. Next, it was immersed in a 64°C boric acid aqueous solution 1 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water for 110 seconds. Next, it was immersed in a 67°C boric acid aqueous solution 2 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water for 30 seconds. Thereafter, it was washed with pure water at 10°C and dried at 80°C to obtain a polarizing film. The thickness of the obtained polarizing film was 7 μm.
[0346] Furthermore, a cycloolefin film (COP film) with a thickness of 25 μm and a hard coating layer was attached to one side of the obtained polarizing film with the surface opposite to the hard coating layer via a water-based adhesive (thickness 0.1 μm), and dried at 90° C. to obtain a linear polarizing plate 1 having a laminated structure of COP film / water-based adhesive (adhesive layer) / polarizer. It should be noted that the water-based adhesive was prepared by adding 3 parts of acetoacetyl-modified polyvinyl alcohol (Z-200, manufactured by Nippon Gosei) and 1.5 parts of a water-soluble polyamide epoxy resin (Sumirez Resin 650, manufactured by Sumika ChemteX, an aqueous solution with a solid content concentration of 30%) to 100 parts of water.
[0347] (Manufacturing of λ / 4 Phase Difference Layer)
[0348] A coating liquid containing a rod-shaped and polymerizable nematic liquid crystal monomer is coated on a transparent resin substrate for λ / 4 orientation laminated with an orientation film, and cured while maintaining the refractive index anisotropy, thereby obtaining a retardation layer with a thickness of 1 μm on the transparent resin substrate. The obtained λ / 4 retardation layer has a light transmittance of 0% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm.
[0349] (Manufacturing of positive C-plate)
[0350] The vertical alignment film-forming composition was applied to one side of the substrate film so as to have a film thickness of 3 μm, and irradiated with 200 mJ / cm 2 The composition for forming a positive C plate is coated on the vertical alignment layer, and after drying, ultraviolet rays (UV) are irradiated on the coating film to polymerize the polymerizable liquid crystal compound to obtain a positive C plate. The obtained positive C plate has a light transmittance of 80% at a wavelength of 380nm and a light transmittance of more than 90% at a wavelength of 400nm.
[0351] (Manufacturing of Phase Difference Layer Laminate)
[0352] The λ / 4 retardation layer and the liquid crystal layer side of the positive C plate were subjected to corona treatment. Using the second active energy ray-curable composition, the liquid crystal layers were bonded together using a laminator so that the thickness of the cured layer was 2 μm, thereby obtaining a laminate.
[0353] From the positive C plate side of the obtained laminate, an ultraviolet irradiation device (manufactured by Fusion UV Systems Co., Ltd.) was used to irradiate the laminate at a cumulative light intensity of 400 mJ / cm 2(UV-A) is used for ultraviolet irradiation to cure the second active energy ray-curable composition to form a second cured layer, thereby obtaining a phase difference layer stack having a stacked structure of "λ / 4 phase difference layer" (first phase difference layer) / adhesive layer (second cured layer) / "positive C plate" (second phase difference layer).
[0354] <Example 1>
[0355] The oriented film and the transparent resin substrate on the λ / 4 phase difference layer side of the phase difference layer stack obtained were peeled off, and the surface of the linear polarizing plate opposite to the thermoplastic resin film and the liquid crystal layer of the λ / 4 phase difference layer were bonded together using Adhesive 1. It should be noted that the film thickness of the first cured layer composed of Adhesive 1 was 2 μm, and the angle between the transmission axis of the polarizer and the slow axis of the λ / 4 phase difference layer was 45°.
[0356] Next, the oriented film and the transparent resin substrate on the positive C plate side are peeled off to obtain a laminate of Example 1 having a laminate structure of COP film (thermoplastic resin film) / water-based adhesive (adhesive layer) / polarizer / first cured layer (cured layer of adhesive 1) / "λ / 4 phase difference layer" (first phase difference layer) / second cured layer (cured layer of the second active energy ray-curable composition) / "positive C plate" (second phase difference layer). The evaluation results of storage modulus, adhesion and durability at 80°C are shown in Table 3.
[0357] <Examples 2 to 10 and Comparative Examples 1 to 3>
[0358] The laminated bodies of Examples 2 to 11 and Comparative Examples 1 to 3 were prepared in the same manner as in Example 1 except that Adhesives 2 to 10 and Adhesives 11 to 13 were used instead of Adhesive 1. The results are shown in Table 3.
[0359] <Comparative Example 4>
[0360] An acrylic adhesive sheet A with an adhesive layer thickness of 5 μm was bonded to the surface of the linear polarizing plate opposite to the thermoplastic resin film to form an acrylic adhesive layer A. The oriented film and the transparent resin substrate on the λ / 4 phase difference layer side of the phase difference layer stack were peeled off. The liquid crystal layer of the λ / 4 phase difference layer of the phase difference layer stack was bonded to the acrylic adhesive layer A of the linear polarizing plate. The angle between the transmission axis of the polarizing plate and the slow axis of the λ / 4 phase difference layer was 45°.
[0361] Next, the oriented film and the transparent resin substrate on the positive C plate side are peeled off to obtain a laminate of Comparative Example 1 having a laminated structure of COP film (thermoplastic resin film) / water-based adhesive (adhesive layer) / polarizer / acrylic adhesive layer A / "λ / 4 phase difference layer" (first phase difference layer) / second cured layer (cured layer of the second active energy ray-curable composition) / "C plate" (second phase difference layer). The obtained laminate was evaluated for water resistance. The results are shown in Table 3.
[0362] <Comparative Example 5>
[0363] A laminate of Comparative Example 5 was obtained in the same manner as in Comparative Example 4 except that acrylic adhesive sheet B was used to form acrylic adhesive layer B with a thickness of 25 μm instead of acrylic adhesive sheet A being used to form acrylic adhesive layer A with a thickness of 5 μm.
[0364] [Table 3]
[0365]
[0366] Explanation of symbols
[0367] 10 linear polarizing plate; 11 polarizing film; 12 first cured layer; 13 first phase difference layer; 14 second cured layer; 15 second phase difference layer; 16 thermoplastic resin film; 17 adhesive layer; 18 adhesive layer; 21 phase difference showing layer; 22 orientation layer; 23 substrate layer; 24 substrate layer; 25 orientation layer; 26 phase difference showing layer; 30 phase difference layer; 31 substrate layer; 32 orientation layer; 33 phase difference showing layer; 50 phase difference layer stack; 70 stack; 100 stack.
Claims
1. A laminated body, which is a laminated body in which a polarizing film, a first cured layer, and a first phase difference layer are sequentially laminated, wherein the first phase difference layer is a polymer of a polymerizable liquid crystal compound, the thickness of the first phase difference layer is 5 μm or less, and the first cured layer comprises a cured product of a first active energy ray-curable composition, The first active energy ray-curable composition comprises (A) a cationically polymerizable compound and (B) a photocationic polymerization initiator, wherein the amount of the photocationic polymerization initiator (B) is 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the cationically polymerizable compound (A). The cationically polymerizable compound (A) contains 45% by mass or more of an oxetane compound based on the total mass of the cationically polymerizable compound (A).
2. The laminate according to claim 1, wherein The first active energy ray-curable composition contains (C) 0.1 to 3.0 parts by mass of a photosensitizer that exhibits maximum absorption for light having a wavelength longer than 400 nm, based on 100 parts by mass of the cationically polymerizable compound (A). The photosensitizer (C) comprises an anthracene compound represented by the following general formula (I): In the formula, R 1 and R 2 each independently represents an alkyl group having 1 to 6 carbon atoms or an alkoxyalkyl group having 2 to 12 carbon atoms, and R 3 It represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
3. The laminate according to claim 1 or 2, wherein: The oxetane compound is at least one selected from 3-ethyl-3-hydroxymethyloxetane, xylenebisoxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and 3-ethyl-3-(cyclohexyloxymethyl)oxetane.
4. The laminate according to claim 1 or 2, wherein: The cationically polymerizable compound (A) contains 10% by mass or more and 50% by mass or less of an alicyclic epoxy compound based on the total mass of the cationically polymerizable compound (A).
5. The laminate according to claim 1 or 2, wherein: The photocationic polymerization initiator (B) is at least one ionic compound selected from aromatic sulfonium salts and aromatic iodonium salts.
6. The laminate according to claim 1 or 2, wherein: The first active energy ray-curable composition has a viscosity of 200 mPa·s or less at 25° C.
7. The laminate according to claim 1 or 2, wherein: The first active energy ray-curable composition satisfies the following formula (1): (J A / J B ) ×100≥60(%) (1) J A It represents the amount of heat measured by a differential scanning calorimeter when ultraviolet rays having a peak at a wavelength of 365 nm are irradiated to the first active energy ray-curable composition through a substrate having a light transmittance of 0% to 10% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm. The unit of the heat is mJ / g. J B It represents the amount of heat measured by a differential scanning calorimeter when ultraviolet rays having a peak at a wavelength of 365 nm are irradiated to the first active energy ray-curable composition without passing through the substrate. The unit of the heat is mJ / g.
8. The laminate according to claim 1 or 2, wherein: The first cured material layer has a storage modulus of 300 MPa or more at 80°C.
9. The laminate according to claim 1 or 2, wherein: The first cured material layer has a thickness of 0.5 μm or more and 10 μm or less.
10. The laminate according to claim 1 or 2, wherein: The first retardation layer has a light transmittance of 0% or more and 50% or less at a wavelength of 380 nm, and a light transmittance of 30% or more at a wavelength of 400 nm.
11. The laminate according to claim 1 or 2, wherein The first retardation layer has a light transmittance of 0% or more and 10% or less at a wavelength of 380 nm, and a light transmittance of 30% or more at a wavelength of 400 nm.
12. The laminate according to claim 1 or 2, wherein: A second cured material layer and a second retardation layer are sequentially stacked on the side of the first retardation layer opposite to the first cured material layer. The second cured layer includes a cured product of a second active energy ray-curable composition, and at least one of the first retardation layer and the second retardation layer has a light transmittance of 0% to 10% at a wavelength of 380 nm and a light transmittance of 30% or more at a wavelength of 400 nm.
13. The laminate according to claim 12, wherein The first phase difference layer is a 1 / 2 wavelength phase difference layer, and the second phase difference layer is a 1 / 4 wavelength phase difference layer.
14. The laminate according to claim 12, wherein The first phase difference layer is a 1 / 2 wavelength phase difference layer or a 1 / 4 wavelength phase difference layer, and the second phase difference layer is a positive C plate.
15. The laminate according to claim 12, wherein At least one of the first retardation layer and the second retardation layer includes a liquid crystal layer having a retardation-appearing property.
16. The laminate according to claim 12, wherein At least one of the first retardation layer and the second retardation layer has a thickness of 0.5 μm or more and 50 μm or less. 17 . A circularly polarizing plate comprising the laminate according to claim 1 . 18 . An image display device comprising an image display panel and the laminate according to claim 1 , which is arranged on a viewing side of the image display panel.
19. The image display device according to claim 18, wherein: The laminate is arranged in an orientation in which the polarizing film is located on the viewing side. 20 . An organic electroluminescent display device, comprising the image display device according to claim 18 or 19.